2023
DOI: 10.1186/s12866-023-02782-4
|View full text |Cite
|
Sign up to set email alerts
|

Lacticaseibacillus casei T1 attenuates Helicobacter pylori-induced inflammation and gut microbiota disorders in mice

Abstract: Probiotics are defined as live microbial food elements that are beneficial to human health. Lacticaseibacillus casei T1 was considered to have potential as a bioactive ingredient in functional foods, which was isolated from kurut. Previous research by our group proved that L. casei T1 could prevent inflammatory responses caused by Helicobacter pylori. This study aimed to investigate whether treatment with L. casei T1 resulted in a suppressive effect on H. pylori-induced oxidative stress and inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 87 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…As intestinal pathogens have shown increased drug resistance, gastrointestinal discomfort and liver damage in humans and animals has been a hot topic. Probiotics not only provide resistance to gastrointestinal pathogens and improve immunity but also improve the gastrointestinal flora [30]. In this study, W. cibaria P-8 showed excellent inhibition against Pseudomonas aeruginosa Z1, Salmonella H9812, Acinetobacter baumannii C1, and MRSA, with the highest inhibitory activity against E. coli B2.…”
Section: Discussionmentioning
confidence: 59%
“…As intestinal pathogens have shown increased drug resistance, gastrointestinal discomfort and liver damage in humans and animals has been a hot topic. Probiotics not only provide resistance to gastrointestinal pathogens and improve immunity but also improve the gastrointestinal flora [30]. In this study, W. cibaria P-8 showed excellent inhibition against Pseudomonas aeruginosa Z1, Salmonella H9812, Acinetobacter baumannii C1, and MRSA, with the highest inhibitory activity against E. coli B2.…”
Section: Discussionmentioning
confidence: 59%
“…It has also been suggested that eradicating H. pylori from the body may be an important treatment for type 2 diabetes ( Shi et al., 2018 ; Shi and Chen, 2021 ). Firstly, H. pylori infection can lead to chronic inflammation of the stomach lining and abnormal secretion of gastric acid, which can affect the digestion of food and absorption of nutrients, which in turn affects metabolism and insulin secretion ( Pachathundikandi et al., 2023 ; Yu et al., 2023 ). Secondly, H. pylori infection can also affect the internal environment of the gastrointestinal tract and promote chronic low-grade inflammation, thereby inducing an inflammatory and immune response in the body, which further affects insulin sensitivity ( Azami et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%